The Balkan Wars 1912-1913 as a cause of the development of “hot nationalism” in the Balkans. The outline of the problem - Gibas-Krzak, Danuta (Balcanica Posnaniensia. Acta et studia, 2012)
<span style="font-family: 'Times New Roman','serif'; font-size: 12pt; mso-fareast-font-family: Calibri; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA; mso-fareast-theme-font: minor-latin;" lang="EN-US">The aim of this article is to examine the origin of “hot nationalism” in the Balkans. Undoubtedly, this kind of nationalism was the final element of the Balkan Wars, that erupted in 1912. The author presents the hypothesis that all Balkan conflicts have in common many factors. First of all, they were leading to develop of the modern nationalism. The ethnic cleansing, which were conducted during the Balkans Wars became the origin of the next Balkan conflicts in XX and XXI centuries. Furthermore, the most important acts of cruelty, violations, rapes, murders are being described along with the overall as it is being manifested in the case of Macedonia. The crucial source of this article constitutes The other Balkan Wars. A 1913 Carnegie Endowment inquiry in retrospect with a new introduction and reflections on the present conflict by George F. Kennan, written in Washington 1993, based on Carnegie Commission Report (1914), whose authors emphasized that “hot nationalism” manifested itself on the field of battle, drew on deeper traits of character inherited, presumably, from a distant tribal past, a tendency to view the outsider, with dark suspicion, and to see the political opponent as a fearful and implacable enemy to be rendered harmless only by total and unpitying destruction. The author asks the question if the “Eastern nationalism”, the most ferocious nationalism, still causes the threat to the security not only in the South Europe but also in the Old Continent?